Pengaruh Motivasi Dan Pengetahuan Mahasiswa Akuntansi Tentang Pajak Terhadap Pilihan Berkarir Sebagai Konsultan Pajak dengan Pemahaman Tringa Sebagai Variabel Moderasi - Suyanto; Hidwan, Uun Julfiana (Universitas Pendidikan Ganesha, 2023)
The problem of limited tax consultants in Indonesia is indirectly related to educational institutions or universities that bring accounting students to work as tax consultants. Therefore, this study examines the influence of tax motivation and knowledge on career choices as tax consultants, and the understanding of tringa as a moderating variable. The data used in this study was primary data covering 181 respondents of accounting students of Tamansiswa University throughout Indonesia using questionnaires with purposive sampling techniques. The results showed that tax motivation and knowledge positively affect the career selection of tax consultants. Understanding Tringa can strengthen the influence of tax motivation and knowledge on the career choice of a tax consultant